Qualidade do leite: Utopia sem um programa sério de monitoramento da ocorrência de mastite bovina - Langoni, Hélio [UNESP] (2013)
Bovine mastitis is still a costly issue in dairy farms, besides public health aspects considering the pathogen transmission to humans. Its multiple etiology with a high number of pathogens involved, demands a rigorous control program for monitoring and milk quality control, based on diagnostic actions and epidemiological vigilance regarding parameters which indirectly are associated with the occurrence of mastitis in dairy herds, as the California Mastitis Test (CMT) and Somatic Cell Count (SCC/mL of milk), of individual milk samples obtained from each cow, and from bulk tank which also allows the Total Bacteria Count (TBC), usually related to the incidence of mastitis, especially in subclinical cases. It is important to reinforce the microbiological milk exam, also to stress the importance of the milking process as a critical point, and to determine risk factors for mastitis. Based on these aspects, this review is presented with the aim to obtain high quality milk products, compromising the personal enrolled in milk production to be conscious that milk quality depends on all, inclusive the consumers which are the final element in the milk production chain.